Experimental determination of the influence of oxygen on the PRESAGE® dosimeter. (6th January 2016) - Alqathami, Mamdooh; Blencowe, Anton; Ibbott, Geoffrey
Abstract: It is generally accepted that the PRESAGE ® radiochromic dosimeter is not sensitive to oxygen, however, this claim has not been supported or verified experimentally. Therefore, the aim of this study was to experimentally determine the potential influence of oxygen on dose sensitivity of the PRESAGE ® dosimeter and its reporting system. Batches of PRESAGE ® and its radical initiator-leuco dye reporting system were prepared in aerobic and anaerobic conditions. The anaerobic batches were deoxygenated by bubbling nitrogen through the dosimeter precursors or reporting system for 10 min. The dosimeters and reporting systems were prepared in spectrophotometric cuvettes and glass vials, respectively, and were irradiated with 6 MV photons to various radiation doses. Changes in optical density of the dosimeters and reporting system before and after irradiation were measured using a spectrophotometer. The overall results show that oxygen has some influence on the dosimetric characteristics of PRESAGE ®, although the radical initiator does appear to oxidize the leucomalachite green even in the presence of oxygen. Deoxygenation of the reporting system leads to an increase in sensitivity to radiation dose by 30% when compared to the non-deoxygenated system. A minor increase in sensitivity ( 5%) was also achieved by deoxygenating the PRESAGE ® precursor prior to casting. In addition, dissolved oxygen measurements revealed low levels of dissolved oxygen (0.40 ± 0.04 mg l −1 ) in the polyurethane precursor used to fabricate the PRESAGE ® dosimeters, as compared to water (8.60 ± 0.03 mg l −1 ) and the reporting system alone (1.30 ± 0.10 mg l −1 ). The results suggest that the presence of oxygen does not inhibit the radiochromic properties of the PRESAGE ® system. However, deoxygenation of the dosimeter precursors prior to casting improves the dosimeters dose sensitivity by 5%, which might be particularly useful for measuring low radiation doses. Nevertheless, we believe this is not sufficient enough to recommend the deoxygenation of commercial PRESAGE ® precursor prior to casting. In addition, there were no observed changes in the dose linearity, absorption spectrum and post-response photofading characteristics of the PRESAGE ® under the conditions investigated.